Thermally conductive mullable silicone rubber composition and thermally conductive sheet

By using the thermal conductivity of a specific component, the existing heat sink has solved the problem of high contact thermal resistance and reduced insulation in the heat sink, and a heat sink with excellent thermal conductivity, strength and insulation is achieved, with moderate hardness and low contact thermal resistance.

CN119790109APending Publication Date: 2025-04-08SHIN ETSU CHEMICAL CO LTD

Patent Information

Application Number
CN202380063375.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-05
Filing Date
2023-08-28
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing high-hardness heat sink cannot obtain efficient heat conduction due to high contact thermal resistance. At the same time, the low-hardness/high-hardness composite sheet is prone to thinning under high pressure, resulting in a decrease in insulation.

Method used

The thermal conductivity-kneaded silicone rubber compositions containing specific alkenyl organopolysiloxanes, organohydrogen polysiloxanes, thermal conductivity fillers, platinum group metal catalysts and addition reaction control agents are used to improve the thermal conductivity and insulation of the composition and reduce contact thermal resistance by uniformly dispersing the thermal conductivity and modified polysiloxanes.

Benefits of technology

It has achieved a heat sink with excellent thermal conductivity, strength and insulation, with moderate hardness and low contact thermal resistance, and excellent long-term stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides a thermally conductive mullable silicone rubber composition comprising (A) (A-1) a raw rubber-like organopolysiloxane having alkenyl groups only at both ends of a molecular chain, (A-2) a raw rubber-like organopolysiloxane having alkenyl groups at both ends and a side chain of a molecular chain, and (A-3) a liquid organopolysiloxane having two or more alkenyl groups per molecule; (B) (B-1) an organohydrogenpolysiloxane having 2-5 hydrosilyl groups in one molecule only in the side chain of the molecular chain, and (B-2) an organohydrogenpolysiloxane having two or more hydrosilyl groups in one molecule and two of the hydrosilyl groups at the ends of the molecular chain; (C) a thermally conductive filler; (E) an addition reaction catalyst; and (F) an addition reaction control agent. The present invention provides a thermally conductive mullizable silicone rubber composition from which a heat sink having low thermal contact resistance and excellent long-term stability can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a heat conductive millable silicone rubber composition and a heat conductive sheet. Background Art

[0002] Heat dissipation components and integrated circuit elements used in various electronic devices may cause degradation of characteristics and shortened life of the components due to heat generation. In order to dissipate heat smoothly, the key is the configuration of components in electronic devices. In addition, cooling fins are used to force air cooling of heat dissipation components or the entire device, or to release the heat generated in integrated circuit elements to the outside of the element through heat sinks.

[0003] However, in recent years, electronic devices with excellent portability, represented by smart phones and tablet terminals, have developed particularly high integration, and the heat release of the above-mentioned heat-releasing components and integrated circuit elements in the equipment is increasing. Therefore, for the cooling or heat dissipation of such components and elements, the previous cooling means are sometimes not sufficient. In particular, the above-mentioned electronic devices require a cooling method other than forced air cooling so as not to impair their portability. In addition, materials with poor thermal conductivity are used in the printed substrates that form the components, so the previous heat sinks cannot fully release the heat generated in the components to the substrate. In response to this, a method is adopted: a heat sink or heat pipe of a natural cooling type or a forced cooling type is set near the component, and the heat generated by the component is transferred to the heat sink via a heat dissipation medium to dissipate the heat.

[0004] In order to make the heat conduction between the component and the heat sink better, a heat sink with a thickness of about 0.2 to 10.0 mm is used as the heat dissipation medium of the above method. As a heat sink, a heat sink is known in which a highly filled and high-hardness silicone rubber layer is reinforced with a cloth-like reinforcing material such as glass cloth (Patent Document 1). The rubber layer of this heat sink has high hardness and is responsible for heat conduction, and also has the function of ensuring insulation, which is very valuable. However, in order to prevent the insulation from decreasing due to thickness changes caused by pressure during installation, the insulating heat sink has to become harder, so the adhesion between the electronic components and the heat sink becomes worse, which makes the contact thermal resistance higher, which becomes a problem.

[0005] In order to reduce the contact thermal resistance, a heat sink is proposed in which a low-hardness thermally conductive silicone rubber layer is laminated on the above-mentioned high-hardness thermally conductive silicone rubber sheet reinforced with a reinforcing material (Patent Document 2). However, in the case of this composite heat sink, the low-hardness layer is compressed and deformed due to pressure, so that the insulation property is sometimes reduced due to filmization or cracking / breaking of the low-hardness layer.

[0006] In addition, in order to achieve both excellent strength and high thermal conductivity, a thermally conductive silicone composite sheet has been proposed in which a thermally conductive silicone cured product is laminated on both surfaces of a metal foil (Patent Documents 3 and 4).

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2015-233104

[0010] Patent Document 2: Japanese Patent Application Publication No. 2014-193598

[0011] Patent Document 3: Japanese Patent Application Publication No. 2013-095023

[0012] Patent Document 4: Japanese Patent Application Publication No. 2017-092322 Summary of the invention

[0013] 1. Technical issues to be resolved

[0014] As mentioned above, high-hardness heat sinks have excellent insulation reliability in addition to heat dissipation due to their strength, but they cannot achieve efficient heat conduction due to high contact thermal resistance. In addition, for low-hardness / high-hardness composite sheets, the sheet will become thinner under high pressure, making it difficult to ensure insulation. In addition, if the method of laminating metal films such as metal foil is applied to silicone rubber sheets, there will be problems such as increased contact thermal resistance, the possibility of poor insulation, and increased manufacturing costs.

[0015] The present invention has been made to solve the above problems, and an object of the present invention is to provide a heat conductive kneadable silicone rubber composition which can obtain a heat sink having excellent thermal conductivity, strength, and insulation, moderate hardness, low contact thermal resistance, and excellent long-term stability.

[0016] (II) Technical solution

[0017] In order to solve the above technical problems, the present invention provides a thermally conductive kneadable silicone rubber composition, characterized in that it comprises:

[0018] (A) 100 parts by mass of a linear organopolysiloxane having an alkenyl group comprising the following components (A-1) to (A-3),

[0019] (A-1) a colloidal organopolysiloxane having alkenyl groups only at both ends of the molecular chain,

[0020] (A-2) a colloidal organopolysiloxane having alkenyl groups at both ends of the molecular chain and in the side chain,

[0021] (A-3) an organopolysiloxane having two or more alkenyl groups in one molecule and being liquid at 25°C;

[0022] (B) an organohydrogenpolysiloxane comprising the following components (B-1) and (B-2): an amount such that the total amount of the hydrosilyl groups in the component (B) is 0.5 to 4.0 mol per 1 mol of the total amount of the alkenyl groups in the component (A);

[0023] (B-1) an organohydrogenpolysiloxane having hydrosilyl groups only in side chains of the molecular chain and having 2 to 5 hydrosilyl groups in one molecule,

[0024] (B-2) an organohydrogenpolysiloxane having two or more hydrosilyl groups in one molecule and two of these hydrosilyl groups at the ends of the molecular chain;

[0025] (C) thermally conductive filler: 150 to 2,400 parts by mass;

[0026] (E) an addition reaction catalyst: an amount of 0.01 to 1,000 ppm calculated as the atomic mass of the platinum group metal; and

[0027] (F) Addition reaction control agent: effective amount.

[0028] According to the thermally conductive kneadable silicone rubber composition of the present invention, a heat sink having excellent thermal conductivity, strength, and insulation properties, having appropriate strength, low contact thermal resistance, and excellent long-term stability can be obtained.

[0029] In this case, it is preferred that the proportion of particles having a particle size of 45 μm or more contained in the component (C) is 5% by mass or less.

[0030] When such a thermally conductive kneadable silicone rubber composition is applied to obtain a thermally conductive sheet, the thermally conductive filler (filler) does not protrude from the coating surface to impair the smoothness of the sheet surface, nor does the contact thermal resistance increase.

[0031] The composition preferably further comprises 5 to 100 parts by mass of a mono-end trialkoxysilyl-modified polysiloxane represented by the following formula (1) as the wetting agent component (D).

[0032] [Chemical formula 1]

[0033]

[0034] In formula (1), R 1 It is an alkyl group having 1 to 6 carbon atoms, and n is an integer of 5 to 100.

[0035] By blending such a component (D), the component (C) can be hydrophobized during the preparation of the composition, thereby improving wettability with the component (A) and allowing the component (C) to be uniformly dispersed in the matrix of the component (A).

[0036] Furthermore, the present invention provides a thermally conductive sheet comprising a cured product of the thermally conductive kneadable silicone rubber composition and a mesh reinforcing material.

[0037] Such a thermally conductive sheet has excellent thermal conductivity, strength, and insulation properties, has appropriate strength, has low contact thermal resistance, and is also excellent in long-term stability.

[0038] At this time, it is preferred that the meshes of the mesh reinforcing material have been filled.

[0039] Such a thermally conductive sheet can improve the contact at the interface between the reinforcing material and the cured product of the thermally conductive kneadable silicone rubber composition, thereby further reducing the contact thermal resistance.

[0040] (III) Beneficial effects

[0041] As described above, the thermally conductive kneadable silicone rubber composition of the present invention can be used as a heat conductive sheet suitable for heat dissipation of electronic devices and the like. In addition, the heat conductive sheet comprising the cured product of the kneadable silicone rubber composition and the mesh reinforcement material can be a sheet with low thermal resistance due to good contact without sacrificing insulation assurance. In addition, by controlling the particle size of the thermally conductive material, continuous coating molding can be performed, resulting in the ability to manufacture with a low-cost and simple process, and the product characteristics are also stable for a long time. DETAILED DESCRIPTION

[0042] As described above, there is a demand for the development of a thermally conductive sheet that has excellent heat dissipation and insulation reliability and also has low contact thermal resistance.

[0043] The inventors of the present application have repeatedly conducted in-depth studies on the above-mentioned technical problems and have found that a thermally conductive kneadable silicone rubber composition characterized by comprising the following components (A), (B), (C), (E), and (F) and a thermally conductive sheet using the composition can solve the above-mentioned technical problems, thereby completing the present invention.

[0044] That is, the present invention is a thermally conductive kneadable silicone rubber composition, characterized in that it comprises:

[0045] (A) 100 parts by mass of a linear organopolysiloxane having an alkenyl group comprising the following components (A-1) to (A-3),

[0046] (A-1) a colloidal organopolysiloxane having alkenyl groups only at both ends of the molecular chain,

[0047] (A-2) a colloidal organopolysiloxane having alkenyl groups at both ends of the molecular chain and in the side chain,

[0048] (A-3) an organopolysiloxane having two or more alkenyl groups in one molecule and being liquid at 25°C;

[0049] (B) an organohydrogenpolysiloxane comprising the following components (B-1) and (B-2): an amount such that the total amount of the hydrosilyl groups in the component (B) is 0.5 to 4.0 mol per 1 mol of the total amount of the alkenyl groups in the component (A);

[0050] (B-1) an organohydrogenpolysiloxane having hydrosilyl groups only in side chains of the molecular chain and having 2 to 5 hydrosilyl groups in one molecule,

[0051] (B-2) an organohydrogenpolysiloxane having two or more hydrosilyl groups in one molecule and two of these hydrosilyl groups at the ends of the molecular chain;

[0052] (C) thermally conductive filler: 150 to 2,400 parts by mass;

[0053] (E) an addition reaction catalyst: an amount of 0.01 to 1,000 ppm calculated as the atomic mass of the platinum group metal; and

[0054] (F) Addition reaction control agent: effective amount.

[0055] Hereinafter, the present invention will be described in detail, but the present invention is not limited thereto.

[0056] [Thermal conductive kneadable silicone rubber composition]

[0057] The thermally conductive kneadable silicone rubber composition of the present invention (hereinafter also referred to as "thermally conductive silicone rubber composition") contains: (A) an organopolysiloxane having an alkenyl group and (B) an organohydrogenpolysiloxane, (C) a thermally conductive filler, (E) an addition reaction catalyst, and (F) an addition reaction control agent. It may further contain additives such as (D) a wetting agent as needed.

[0058] Hereinafter, the components contained in the composition of the present invention will be described.

[0059] [(A) Organopolysiloxane having alkenyl group]

[0060] The linear organopolysiloxane having alkenyl groups as component (A) is the main component of the composition of the present invention. Component (A) is characterized by containing the following three components (A-1) to (A-3):

[0061] (A-1) a colloidal organopolysiloxane having alkenyl groups only at both ends of the molecular chain,

[0062] (A-2) a colloidal organopolysiloxane having alkenyl groups at both ends of the molecular chain and in the side chain,

[0063] (A-3) An organopolysiloxane having two or more alkenyl groups in one molecule and being liquid at 25°C.

[0064] In any of the structures of the three types of linear organopolysiloxanes having an alkenyl group, the main chain portion is a linear diorganopolysiloxane composed of a repeating diorganosiloxane unit.

[0065] The alkenyl group of the three organopolysiloxanes is preferably an alkenyl group having 2 to 8 carbon atoms, and examples thereof include vinyl, allyl, propenyl, isopropenyl, butenyl, hexenyl, and cyclohexenyl. Among them, vinyl and allyl groups are preferred, and vinyl groups are particularly preferred.

[0066] In addition, as the functional group other than the alkenyl group bonded to the silicon atom possessed by the above three types of organopolysiloxanes, it is preferable to select a monovalent hydrocarbon group from an alkyl group having 1 to 10 carbon atoms, an alkyl group preferably having 1 to 6 carbon atoms, an aryl group having 6 to 10 carbon atoms, and an aralkyl group having 7 to 10 carbon atoms. For example, alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, heptyl, and octyl; cycloalkyl groups such as cyclopentyl, cyclohexyl, and cycloheptyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; and aralkyl groups such as benzyl, phenethyl, and phenylpropyl. In addition, the functional groups other than the alkenyl group bonded to the silicon atom are not limited to all being the same.

[0067] Specific examples of the organopolysiloxane having an alkenyl group include, for example, an organosiloxane copolymer composed of the following compounds: a dimethylsiloxane-methylvinylsiloxane copolymer having both ends of the molecular chain blocked by trimethylsiloxane groups, a methylvinylpolysiloxane having both ends of the molecular chain blocked by trimethylsiloxane groups, a dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymer having both ends of the molecular chain blocked by trimethylsiloxane groups, a dimethylpolysiloxane having both ends of the molecular chain blocked by dimethylvinylsiloxane groups, a methylvinylpolysiloxane having both ends of the molecular chain blocked by dimethylvinylsiloxane groups, and a Dimethylsiloxane-methylvinylsiloxane copolymers end-capped with dimethylvinylsiloxane groups at both ends, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymers end-capped with dimethylvinylsiloxane groups at both ends of the molecular chain, dimethylpolysiloxane end-capped with divinylmethylsiloxane groups at both ends of the molecular chain, dimethylsiloxane-methylvinylsiloxane copolymers end-capped with divinylmethylsiloxane groups at both ends of the molecular chain, dimethylpolysiloxane end-capped with trivinylsiloxane groups at both ends of the molecular chain, and dimethylsiloxane-methylvinylsiloxane copolymers end-capped with trivinylsiloxane groups at both ends of the molecular chain.

[0068] [(A-1) Colloidal organopolysiloxane having alkenyl groups only at both ends of the molecular chain]

[0069] The component (A-1) is a gel-like organopolysiloxane having alkenyl groups only at both ends of the molecular chain.

[0070] In the present invention, the raw gel state refers to a very high viscosity liquid of 200,000 mPa·s or more at room temperature (25°C), or a non-liquid state (paste or solid state) without self-flowability. In addition, in the present invention, the viscosity refers to the value measured by a rotational viscometer according to the method described in JIS Z8803:2011.

[0071] The degree of polymerization of the component (A-1) is preferably 2,000 to 20,000, more preferably 3,000 to 15,000. The degree of polymerization in the present invention is generally a value calculated from the weight average degree of polymerization in terms of polystyrene measured by gel permeation chromatography (GPC) analysis using toluene as a developing solvent.

[0072] [Measurement conditions]

[0073] Developing solvent: Toluene

[0074] Flow rate: 1mL / min

[0075] Detector: Refractive Index (RI)

[0076] Chromatographic column: KF-805L × 2 (manufactured by Shodex)

[0077] Column temperature: 25°C

[0078] Sample injection volume: 30 μL (toluene solution with a concentration of 0.2 mass %)

[0079] [(A-2) Colloidal organopolysiloxane having alkenyl groups at both ends of the molecular chain and in the side chain]

[0080] The component (A-2) is a gel-like organopolysiloxane having alkenyl groups at both ends of the molecular chain and in the side chain.

[0081] The degree of polymerization of the component (A-2) is preferably 2,000 to 20,000, more preferably 3,000 to 15,000. The number of the side chain alkenyl groups in one molecule is preferably 1 to 200, more preferably 2 to 100.

[0082] [(A-3) Organopolysiloxane having two or more alkenyl groups in one molecule and being liquid at 25°C]

[0083] The component (A-3) is an organopolysiloxane having two or more alkenyl groups in one molecule and being liquid at 25°C. In the present invention, liquid means having autonomous flowability at 25°C.

[0084] The degree of polymerization of the component (A-3) is preferably 100 to 2,000, more preferably 500 to 1,500. The number of alkenyl groups in one molecule is characterized by being 2 or more, preferably 2 to 10, more preferably 2 to 5. The alkenyl group may be located at the end of the molecular chain or at the side chain, and preferably has an alkenyl group only at the end of the molecular chain.

[0085] The structure of the component (A-3) is a linear chain in which the main chain portion is composed of a repeating diorganosiloxane unit.

[0086] The component (A-3) is characterized in that it is liquid at 25° C. The viscosity thereof is preferably 500 to 200,000 mPa·s, more preferably 10,000 to 150,000 mPa·s.

[0087] The blending ratio of (A-1) to (A-3) is preferably 20 to 45% by mass of the component (A-1), 20 to 45% by mass of the component (A-2), and 10 to 40% by mass of the component (A-3), when the total amount of the component (A) is 100% by mass.

[0088] [(B) Organohydrogenpolysiloxane]

[0089] The organohydrogenpolysiloxane as the component (B) reacts with the component (A) and functions as a crosslinking agent.

[0090] The component (B) is characterized by using an organohydrogenpolysiloxane containing two components (B-1) and (B-2):

[0091] (B-1) an organohydrogenpolysiloxane having hydrosilyl groups only in the side chains of the molecular chain and having 2 to 5 hydrosilyl groups in one molecule,

[0092] (B-2) An organohydrogenpolysiloxane having two or more hydrosilyl groups in one molecule, two of which are at the ends of the molecular chain.

[0093] The functional groups other than the hydrogen silyl group of the organohydrogen polysiloxane as the component (B) are preferably monovalent hydrocarbon groups selected from alkyl groups having 1 to 10 carbon atoms, alkyl groups having preferably 1 to 6 carbon atoms, aryl groups having 6 to 10 carbon atoms, and aralkyl groups having 7 to 10 carbon atoms. For example, alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, nonyl, and decyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; aralkyl groups such as benzyl, phenethyl, and phenylpropyl, etc. Among them, in terms of flame retardancy, it is expected that: alkyl groups and aryl groups are preferred, and methyl groups and phenyl groups are more preferred. In addition, the functional groups other than the hydrogen atoms (hydrogen silyl groups) bonded to silicon atoms are not limited to being all the same.

[0094] [(B-1) an organohydrogenpolysiloxane having hydrosilyl groups only in the side chains of the molecular chain and having 2 to 5 hydrosilyl groups in one molecule]

[0095] The component (B-1) is an organohydrogen polysiloxane having hydrosilyl groups only in the side chains of the molecular chain and having 2 to 5, preferably 2 to 4, hydrosilyl groups in one molecule. In the present invention, the term "hydrosilyl groups in the side chains of the molecular chain" means that there is a Si-H bond in the D unit or T unit constituting the polysiloxane main chain, or there is a Si-H bond in the side chain of the polysiloxane.

[0096] The structure of the component (B-1) may be either linear or branched, but is preferably linear.

[0097] The degree of polymerization of the component (B-1) is preferably 4 to 350, more preferably 10 to 200.

[0098] Specific examples of the component (B-1) include organohydrogenpolysiloxane represented by the following formula (o=27, p=2).

[0099] [Chemical formula 2]

[0100]

[0101] [(B-2) an organohydrogenpolysiloxane having two or more hydrosilyl groups in one molecule and two of these hydrosilyl groups at the ends of the molecular chain]

[0102] The component (B-2) is an organohydrogen polysiloxane having 2 or more, preferably 2 to 50, more preferably 2 to 20, hydrogen silyl groups in one molecule, and having 2 of the hydrogen silyl groups at the ends of the molecular chain. The hydrogen silyl group may be present at the end of the main chain (the longest polysiloxane chain) or at the end of the side chain. As described above, in the present invention, the ends of the molecular chain of polysiloxane refer to both the ends of the polysiloxane main chain and the ends of the polysiloxane side chains, and when simply referred to as the two ends, it refers to the two ends of the polysiloxane main chain.

[0103] The structure of the component (B-2) may be either linear or branched, but is preferably linear.

[0104] The degree of polymerization of the component (B-2) is preferably 4 to 200, more preferably 10 to 100.

[0105] Specific examples of the component (B-2) include organohydrogenpolysiloxane represented by the following formula (q=65, r=1).

[0106] [Chemical formula 3]

[0107]

[0108] The content of the organohydrogenpolysiloxane of the component (B) is an amount such that the total amount of hydrogen silyl groups in the component (B) is 0.5 to 4.0 mol relative to 1 mol of the total amount of alkenyl groups in the component (A), and preferably an amount such that the total amount of hydrogen silyl groups in the component (B) is 0.6 to 3.0 relative to 1 mol of the total amount of alkenyl groups in the component (A). If the content of this component is less than 0.5 mol, the viscosity of the obtained thermally conductive silicone rubber sometimes becomes stronger, and blocking sometimes occurs when it is made into a roll. In addition, since the thickness change rate increases during compression, the insulation may decrease. On the other hand, if the content of this component is in a slightly excessive state of greater than 4.0 mol and less than 6.0 mol, the applicability period of the obtained thermally conductive silicone rubber composition may be shortened, and solidification may occur before the curing process. In addition, since the obtained cured product becomes hard, the contact impedance cannot be fully reduced. Furthermore, when the content of this component is in a largely excessive state of 6.0 mol or more, this component which does not participate in the crosslinking reaction acts as a plasticizer, so that the cured product becomes soft and the thickness change rate becomes large, thereby reducing the insulation properties.

[0109] The ratio of the blending amounts of (B-1) and (B-2) is preferably 30 to 95% by mass of the component (B-1) and 5 to 70% by mass of the component (B-2) when the total amount of the component (B) is 100% by mass.

[0110] As described above, by using three (A) components and two (B) components of the present invention together, the crosslinking structure (chain length extension, crosslinking density) of the polysiloxane can be strictly controlled while maintaining good handling properties of the raw gel organopolysiloxane in the (A) component.

[0111] [(C) Thermally conductive filler]

[0112] The component (C) is a thermally conductive filler that imparts thermal conductivity to the thermally conductive silicone composition. Suitable examples of thermally conductive fillers include inorganic powders such as aluminum oxide, zinc oxide, silicon dioxide, silicon carbide, aluminum nitride, and boron nitride. The component (C) may be used alone or in combination of two or more.

[0113] The amount of component (C) to be added is preferably in the range of 150 to 2,400 parts by mass, preferably 200 to 2,300 parts by mass, relative to 100 parts by mass of component (A). If the amount is less than 150 parts by mass, thermal conductivity tends to be insufficient, while if it is more than 2,400 parts by mass, it may be difficult to uniformly blend component (C) into the composition and molding processability may deteriorate.

[0114] The particle size distribution of component (C) is not particularly limited, but preferably, the proportion of particles having a particle size of 45 μm or more is 5% by mass or less, and more preferably 2% by mass or less. If the proportion of particles having a particle size of 45 μm or more is 5% by mass or less, after applying the thermally conductive kneadable silicone rubber composition to obtain a thermally conductive sheet, there is no need to worry about the thermally conductive filler (filling material) protruding from the coating surface and thus impairing the smoothness of the sheet surface, and there is no need to worry about an increase in contact thermal resistance.

[0115] As long as the proportion of particles with a particle size of 45 μm or more in component (C) is 5% by mass or less, fillers having multiple particle size distributions may be used. For example, fillers having convex portions at 1 μm and 10 μm on the particle size distribution curve may be used, or fillers having an average particle size of 5 μm and fillers having an average particle size of 20 μm may be used simultaneously.

[0116] For component (C), the average particle size is preferably 0.1 to 30 μm, more preferably 0.1 to 10 μm. If the average particle size is 30 μm or less, after applying the thermally conductive silicone rubber composition to obtain a thermally conductive sheet, there is no need to worry about the thermally conductive filler protruding from the coating surface and thus damaging the smoothness of the sheet surface, and there is no need to worry about increased contact thermal resistance. If the average particle size is 0.1 μm or more, the thermally conductive filler is easy to obtain.

[0117] The above average particle size can be generally used as the cumulative volume average particle size D in the particle size distribution measurement based on laser diffraction. 50 Specifically, the volume-based cumulative 50% particle size (D 50 The ratio of particles having a specific particle size (for example, a particle size of 45 μm) or more can be determined by the above-mentioned particle size distribution measurement.

[0118] [(D) Wetting agent]

[0119] The thermally conductive silicone rubber composition of the present invention preferably contains a wetting agent (D). The purpose of the component (D) is to hydrophobize the component (C) when preparing the composition, thereby improving the wettability with the component (A) and making the component (C) uniformly dispersed in the matrix composed of the component (A). The component (D) is particularly preferably a single-terminal trialkoxysilyl-modified polysiloxane represented by the following formula (1).

[0120] [Chemical formula 4]

[0121]

[0122] In the above formula (1), R 1 It is an alkyl group having 1 to 6 carbon atoms, and preferably an alkyl group having 1 to 3 carbon atoms. In addition, n is an integer of 5 to 100, and preferably 10 to 50.

[0123] When the component (D) is added, the amount of the component (D) is 5 to 100 parts by mass, and particularly preferably 10 to 60 parts by mass, relative to 100 parts by mass of the component (A). When the proportion of this component is within the above range, there is no concern that oil separation may be induced.

[0124] [(E) Addition reaction catalyst]

[0125] The addition reaction catalyst of the component (E) is used to promote the addition reaction of the alkenyl group bonded to the silicon atom in the component (A) and the hydrosilyl group in the component (B). This addition reaction catalyst is a platinum group metal or a platinum group metal compound. For example, platinum group metals such as platinum, palladium, and rhodium; chloroplatinic acid; alcohol-modified chloroplatinic acid; coordination compounds of chloroplatinic acid with olefins, vinylsiloxanes, or acetylene compounds; platinum group metal compounds such as tetrakis(triphenylphosphine)palladium and tris(triphenylphosphine)rhodium chloride, etc. Among them, platinum group metal compounds are preferred. In the present composition, the content of the component (E) is 0.01 to 1,000 ppm, preferably 0.1 to 500 pp, relative to the component (A), in terms of the atomic mass of the platinum group metal. If the content of this component is too small, the thermally conductive silicone rubber composition obtained may not be sufficiently cured. On the other hand, even if a large amount is used, the curing speed of the silicone rubber composition obtained may not increase, which is economically disadvantageous.

[0126] [(F) Addition reaction control agent]

[0127] The addition reaction control agent is not particularly limited as long as it is a compound that has a curing reaction inhibitory effect on the addition reaction catalyst of the above-mentioned (E) component, and any known addition reaction control agent can be used. Specific examples thereof include: phosphorus-containing compounds such as triphenylphosphine; nitrogen-containing compounds such as tributylamine, tetramethylethylenediamine, and benzotriazole; sulfur-containing compounds; acetylene compounds such as 1-ethynyl-1-cyclohexanol, 3-butyn-1-ol, 2-methyl-3-butyn-2-ol, and 3-methyl-1-tridecyn-3-ol; vinyl-containing siloxanes such as 1,3-divinyl-1,1,3,3-tetramethyldisiloxane and 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane; hydroperoxy compounds; maleic acid derivatives, etc. Since the degree of curing reaction inhibition of the addition reaction controller varies due to its chemical structure, the amount of the addition reaction controller is preferably adjusted to the optimal amount of each addition reaction controller used. By blending the optimal amount of the reaction controller, the composition has excellent long-term storage stability and curability at room temperature. As mentioned above, the blending amount of the (F) component is not particularly limited, and an amount of 50 to 150 times the amount of 1 mole of platinum group metal atoms contained in the addition reaction catalyst of the (E) component can be blended. For example: When an acetylene compound such as 3-methyl-1-tridecan-3-ol is used as the (F) component, it is preferably blended in an amount within the above range.

[0128] [Other ingredients]

[0129] The thermally conductive silicone rubber composition of the present invention may be further blended with other components as required, for example, heat resistance enhancers such as iron oxide, viscosity modifiers such as silicon dioxide, colorants, release agents, and other arbitrary components.

[0130] [Cured product of thermally conductive silicone rubber composition and its hardness]

[0131] The thermally conductive silicone rubber composition can be cured under known conditions. The curing conditions are not particularly limited, and may be, for example, 80 to 150° C. for about 30 seconds to 1 hour.

[0132] The hardness of the cured product of the thermally conductive silicone rubber composition is 40 to 70, preferably 50 to 60, in terms of durometer A hardness, which is measured according to the method described in JIS K 6253: 2012. If the hardness is 40 or more, the cured product is not easily deformed by pressure (not easily thinned), and the insulation properties are easily maintained. If the hardness is 70 or less, the contact thermal resistance is sufficiently low, and sufficient heat dissipation properties can be exerted.

[0133] [Thermal conductive sheet]

[0134] The thermally conductive sheet of the present invention comprises: a cured product of the thermally conductive kneadable silicone rubber composition and a mesh reinforcing material.

[0135] Such a thermally conductive sheet comprises a cured product obtained by curing the thermally conductive kneadable silicone rubber composition of the present invention and a mesh reinforcing material, and therefore has excellent thermal conductivity, strength, and insulation, has appropriate hardness, low contact thermal resistance, and excellent long-term stability.

[0136] [Network reinforcement material]

[0137] There is no particular limitation on the mesh reinforcement material used to reinforce the thermally conductive sheet, and examples thereof include inorganic fiber cloths such as glass cloth and ceramic cloth, or organic fiber cloths such as nylon and polyester, or the above-mentioned composite materials. In order to make the interface between the reinforcement material and the cured product of the thermally conductive silicone rubber composition contact well and thus reduce the contact thermal resistance, it is preferred to fill the mesh of the reinforcement material. By filling the mesh, in addition to filling the opening of the mesh reinforcement material so that the adhesion strength between the mesh reinforcement material and the cured product of the thermally conductive silicone rubber composition is increased, the mesh of the reinforcement material is fixed so that the shape can also be made more stable.

[0138] The mesh material is not particularly limited, and for example, addition reaction curing type and peroxide curing type materials can be used. Among them, thermally conductive silicone rubber material is the best. As the thermally conductive silicone rubber material, there is no requirement for the curing type, and the above-mentioned thermally conductive mixable silicone rubber composition can be used, and other materials can also be used. If the thermally conductive mixable silicone rubber composition used to obtain a cured product for constituting the thermally conductive sheet is the same as the filling mesh material, then the thermal conductivity, strength, and insulation are more excellent, it has a moderate hardness, and the contact thermal resistance is small, and the productivity is also improved, so it is particularly preferred.

[0139] The thickness of the reinforcing material is, for example, 20 to 100 μm, more preferably 30 to 80 μm. If the thickness of the reinforcing material is 20 μm or more, the strength of the thermally conductive sheet is sufficient. On the other hand, if the thickness of the reinforcing material is 100 μm or less, the thermal conductivity is sufficient.

[0140] [Contact thermal resistance]

[0141] The thermal contact resistance of the thermally conductive sheet of the present invention to the adherend is preferably 40 mm / s when measured under the conditions of 50°C / 700 kPa according to ASTM D5470. 2 · K / W or less, more preferably 5 to 35 mm 2 K / W. If the contact thermal resistance is 40mm 2 K / W or less, the adherend and the thermally conductive sheet will be more closely attached, and the thermal conductivity will be good. The thermal contact resistance of the thermally conductive sheet to the adherend can be determined by the method described in the examples described below.

[0142] [Thickness change rate of thermal conductive sheet]

[0143] The thermally conductive sheet becomes thinner as pressure is applied, which reduces the insulation performance. In other words, in terms of maintaining the insulation performance, the smaller the thickness change rate of the thermally conductive sheet is, the better.

[0144] For the thermally conductive sheet of the present invention, the thickness change rate after applying a pressure of 700 kPa to the thermally conductive sheet and compressing for 20 minutes is 20% or less of the initial thickness, and more preferably 10% or less. If the thickness change rate is 20% or less, the thickness change rate becomes small under high-voltage installation, so it is easy to maintain insulation properties.

[0145] [Manufacturing of thermally conductive sheets]

[0146] The method for producing the thermally conductive sheet of the present invention is not particularly limited, and a press method, a coating method, and the like can be applied. Generally, the coating method is more effective.

[0147] When the thermally conductive sheet is produced by a coating method, for example, the following steps (1) to (3) are performed.

[0148] (1) Process for preparing the coating composition:

[0149] In addition to the components (A) to (F) and the solvent, additives and the like are further added and mixed as required. The obtained mixture is treated as required and stirred and mixed to prepare a coating composition.

[0150] (2) The process of filling the mesh:

[0151] A step of applying the coating composition obtained in the above step to a reinforcing material as required, and heating as required to obtain a reinforcing material with filled meshes.

[0152] (3) Coating process:

[0153] A step of applying a thermally conductive silicone rubber composition to a reinforced material having filled pores, and then heating the composition to laminate (apply) a cured product of the composition.

[0154] <Preparation of coating composition>

[0155] First, the linear organopolysiloxane having an alkenyl group as component (A), the thermally conductive filler as component (C), and the wetting agent as component (D) are kneaded while being heated to a temperature of about 100° C. or higher as required using a kneading machine, a Banbury mixer, a planetary mixer, a Shinagawa mixer, or the like. In this kneading step, reinforcing silica such as fumed silica and precipitated silica, and flame retardants such as platinum, titanium oxide, and benzotriazole may be added / mixed as required.

[0156] The uniform mixture obtained in the kneading step is cooled to room temperature and filtered through a strainer, etc. Then, a two-roll mixer, a Shinagawa mixer, etc. may be used to add / mix the following into the mixture as needed: colorants such as organic pigments and inorganic pigments; heat resistance improvers such as iron oxide and cerium oxide; internal mold release agents; catalysts, etc.

[0157] To the composition obtained in the re-kneading step, a curing agent and an acetylene compound addition reaction control agent such as 1-ethynyl-1-cyclohexanol (component (F)), a catalyst (component (E)), etc. are added to prepare a coating composition, and after further adding a solvent such as toluene, mixing is carried out using a mixer such as a planetary mixer and a kneading machine, and finally a crosslinking agent (component (B)) is added and further mixed to prepare a coating composition.

[0158] <Filling the holes in the reinforcement material>

[0159] The coating composition obtained by the above process is applied to the above reinforcing material to fill the meshes. After continuously applying to the reinforcing material using a coating device such as a knife coater or a kiss coater which is equipped with a drying furnace, a heating furnace and a winding device, the solvent is dried / evaporated, and in the case of an addition reaction curing type, the composition is heated to 80 to 200°C, preferably to about 100 to 150°C, and in the case of a peroxide curing type, the composition is heated to 100 to 200°C, preferably to about 110 to 180°C, thereby obtaining a reinforcing material with filled meshes.

[0160] <Coating>

[0161] The coating composition that will become the cured product of the thermally conductive silicone rubber composition is applied to one or both sides of the mesh-filled reinforcing material obtained through the above process. After continuously applying it to one side of the mesh-filled reinforcing material using a coating device such as a knife coater or a kiss coater that is continuously equipped with a drying furnace, a heating furnace, and a winding device, the solvent is dried / evaporated, and the composition is heated to 80 to 200°C, preferably about 100 to 150°C, to perform lamination.

[0162] Example

[0163] The present invention will be described in detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples. The average degree of polymerization, viscosity, particle size, and average particle size were measured by the above-mentioned methods.

[0164] The materials used in Examples and Comparative Examples are as follows.

[0165] [(A) ingredient: vinyl polysiloxane]

[0166] (A-1) an organopolysiloxane rubber having 7998 dimethylsiloxane units and 2 dimethylvinylsiloxane units in one molecule and an average degree of polymerization of 8,000

[0167] (A-2) an organopolysiloxane raw rubber having 7960 dimethylsiloxane units, 38 methylvinylsiloxane units and 2 dimethylvinylsiloxane units in one molecule and having an average degree of polymerization of 8,000

[0168] (A-3) An organopolysiloxane having 1,128 dimethylsiloxane units and 2 dimethylvinylsiloxane units in one molecule, an average degree of polymerization of 1,130, a liquid state at 25° C., and a viscosity of 105,000 mPa·s.

[0169] [Component (B): Hydrogen polysiloxane]

[0170] The following (B-1) and (B-2) were mixed so that the ratio was 3:1.

[0171] (B-1) Methyl hydrogen polysiloxane represented by the following formula

[0172] An organohydrogen polysiloxane represented by the following formula (o=27, p=2) as a crosslinking agent:

[0173] [Chemical formula 5]

[0174]

[0175] (B-2) Methyl hydrogen polysiloxane represented by the following structural formula

[0176] An organohydrogenpolysiloxane represented by the following formula (q=65, r=1) as a crosslinking agent:

[0177] [Chemical formula 6]

[0178]

[0179] [(C) ingredient: thermally conductive filler]

[0180] (C-1) Amorphous aluminum oxide having an average particle size of 1 μm and a particle size of 45 μm or more in an amount of 0.8 mass %

[0181] (C-2) Spherical aluminum oxide having an average particle size of 1 μm and a particle size of 45 μm or more in an amount of 0.6% by mass

[0182] (C-3) Spherical aluminum oxide having an average particle size of 10 μm and a particle size of 45 μm or more in an amount of 1.2% by mass

[0183] (C-4) Boron nitride having an average particle size of 5 μm and a particle size of 45 μm or more in an amount of 0.9 mass %

[0184] (C-5) Aluminum nitride having an average particle size of 1 μm and a particle size of 45 μm or more in an amount of 1.1% by mass

[0185] (C-6) Spherical aluminum oxide having an average particle size of 10 μm and a particle size of 45 μm or more in an amount of 8.3% by mass

[0186] [(D) ingredient: wetting agent]

[0187] A dimethylpolysiloxane having a trimethoxysilyl group-terminated dimethylpolysiloxane having the following formula and an average degree of polymerization of 30

[0188] [Chemical formula 7]

[0189]

[0190] [Component (E): platinum group metal catalyst]

[0191] 5 mass% chloroplatinic acid 2-ethylhexanol solution

[0192] [Component (F): addition reaction control agent]

[0193] 3-Methyl-1-tridecyn-3-ol

[0194] [Component (G): Peroxide Curing Agent (for Comparative Example)]

[0195] Bis(4-methylbenzoyl)peroxide

[0196] Mesh reinforcement material: Glass cloth equivalent to IPC standard 1080 (thickness: 55μm).

[0197] [Examples 1 to 5 and Comparative Examples 1 to 5]

[0198] The thermally conductive sheets of Examples 1 to 5 and Comparative Examples 1 to 5 were produced in the following manner.

[0199] [Preparation of thermally conductive silicone rubber composition]

[0200] (Preparation Example 1)

[0201] The components in the amounts (parts by mass) shown in Tables 1 and 2 were charged into a Banbury mixer and kneaded for 20 minutes to prepare thermally conductive silicone rubber compositions (a) to (d) and (k) to (o).

[0202] [Manufacturing of thermally conductive sheets]

[0203] (Manufacturing Example 1) Filling the mesh of glass cloth

[0204] The thermally conductive silicone rubber composition obtained in the above (Preparation Example 1) was used as a composition for filling meshes, and 20% by mass of toluene was added thereto, and kneaded using a planetary mixer to prepare a coating material. The coating material was applied to one side of a glass cloth using a comma coater to fill the meshes of the glass cloth. Then, it was dried at 80°C for 10 minutes and further cured at 170°C for 15 minutes. The thickness of the glass cloth with the filled meshes was 80 μm.

[0205] (Manufacturing Example 2) Coating on a glass cloth with filled mesh (heat conductive sheet with a total thickness of 0.2 mm)

[0206] Toluene in an amount of 20% by mass was added to the thermally conductive silicone rubber composition obtained in the above (Preparation Example 1), and mixed using a planetary mixer to obtain a coating material. The coating material was applied to one side (surface) of the glass cloth with the meshes filled in the above using a comma coater in such a way that the thickness after curing became 0.06 mm, and then cured and wound up. Then, the other side (back side) was similarly coated and wound up after curing, thereby obtaining a thermally conductive sheet with a total thickness of 0.2 mm. The comma coater and coating and curing conditions used were the same as those in the above-mentioned mesh filling (Preparation Example 1).

[0207] (Manufacturing Example 3) Coating on a glass cloth with filled mesh (heat conductive sheet with a total thickness of 0.3 mm)

[0208] Toluene in an amount of 20% by mass was added to the thermally conductive silicone rubber composition obtained in the above (Preparation Example 1), and mixed using a planetary mixer to obtain a coating material. The coating material was applied to one side (surface) of the glass cloth with the meshes filled in the above-obtained glass cloth using a comma coater in a manner such that the thickness after curing was 0.11 mm, and then cured and wound up. Then, the other side (back side) was similarly coated, and wound up after curing, thereby obtaining a thermally conductive sheet with a total thickness of 0.3 mm. The comma coater and coating and curing conditions used were the same as those in the above-mentioned mesh filling (Preparation Example 1).

[0209] (Manufacturing Example 4) Coating on a glass cloth with filled mesh (heat conductive sheet with a total thickness of 0.45 mm)

[0210] Toluene in an amount of 20% by mass was added to the thermally conductive silicone rubber composition obtained above (Preparation Example 1), and mixed using a planetary mixer to obtain a coating material. The coating material was applied to one side (surface) of the glass cloth with the mesh filled above using a comma coater in a manner such that the thickness after curing was 0.185 mm, and then cured and wound up. Then, the other side (back side) was similarly coated, and wound up after curing to obtain a thermally conductive sheet with a total thickness of 0.45 mm. The comma coater and coating and curing conditions used were the same as those for the mesh filling (Preparation Example 1).

[0211] [Evaluation methods of various characteristics]

[0212] The various properties of the thermally conductive sheet were measured by the following methods. The measurement results are shown in Tables 1 and 2.

[0213] [General characteristics]

[0214] <Initial thickness>

[0215] The measurement was performed using a digital thickness gauge (Digimatic Thickness Gauge) manufactured by Mitutoyo Corporation.

[0216] <Thermal resistance and contact thermal resistance / thickness under pressure>

[0217] The thermal resistance of the thermally conductive sheet is measured according to ASTM D 5470 using the following procedure.

[0218] Thermally conductive sheets with thicknesses of 0.2 mm, 0.3 mm, and 0.45 mm were prepared and pressurized at 50°C / 700 kPa to measure the thermal resistance of the thermally conductive sheets of various thicknesses. Furthermore, the contact thermal resistance was obtained by plotting the thickness (mm) of the thermally conductive sheet when pressurized (below 700 kPa) on the horizontal axis and the thermal resistance on the vertical axis.

[0219] <Thickness change rate>

[0220] The thickness of the thermally conductive sheet under pressure was measured in the same manner as the thermal resistance measurement, and the thickness change rate was calculated using the following calculation formula.

[0221] [Mathematical formula 1]

[0222]

[0223] <Hardness of Cured Product of Thermally Conductive Silicone Rubber Composition>

[0224] Using each cured product, a sample for hardness measurement was separately prepared, and the hardness was measured using a type A durometer in accordance with JIS K 6253:2012 (measurement temperature: 25° C.).

[0225] Hereinafter, the thermally conductive silicone rubber composition obtained in (Preparation Example 1) was used as a mesh-filling composition to fill the meshes of the glass cloth according to (Preparation Example 1), and the glass cloth whose meshes had been filled was coated according to (Preparation Example 2) to (Preparation Example 4), thereby preparing thermally conductive sheets of Examples 1 to 5 and Comparative Examples 1 to 5.

[0226] <Example 1>

[0227] After the meshes of the glass cloth are filled with the composition (a), the glass cloth whose meshes are filled is coated with the composition (a) to obtain a thermally conductive sheet.

[0228] <Example 2>

[0229] After the meshes of the glass cloth are filled with the composition (b), the glass cloth whose meshes are filled is coated with the composition (b) to obtain a thermally conductive sheet.

[0230] <Example 3>

[0231] After the meshes of the glass cloth are filled with the composition (c), the glass cloth whose meshes are filled is coated with the composition (c) to obtain a thermally conductive sheet.

[0232] <Example 4>

[0233] After the meshes of the glass cloth are filled with the composition (d), the glass cloth whose meshes are filled is coated with the composition (d) to obtain a thermally conductive sheet.

[0234] <Example 5>

[0235] After the meshes of the glass cloth are filled with the composition (k), the glass cloth whose meshes are filled is coated with the composition (a) to obtain a thermally conductive sheet.

[0236] <Comparative Example 1>

[0237] After the meshes of the glass cloth are filled with the composition (k), the glass cloth whose meshes are filled is coated with the composition (k) to obtain a thermally conductive sheet.

[0238] <Comparative Example 2>

[0239] After filling the mesh of the glass cloth with the composition (1), the glass cloth with the filled mesh was coated with the composition (1) to obtain a thermally conductive sheet. Since the obtained sheet had very low hardness and strong adhesiveness, the thermal resistance and thickness could not be accurately measured.

[0240] <Comparative Example 3>

[0241] After filling the meshes of the glass cloth with the composition (m), the glass cloth with the filled meshes was coated with the composition (m) to obtain a thermally conductive sheet. However, aggregates of the filler were observed on the surface of the sheet, and the thermal resistance and thickness could not be accurately measured.

[0242] <Comparative Example 4>

[0243] The blending amount of the thermally conductive filler in the composition (n) was too large, and a uniform composition could not be obtained.

[0244] <Comparative Example 5>

[0245] After the meshes of the glass cloth are filled with the composition (o), the glass cloth with the meshes filled is coated with the composition (o) to obtain a thermally conductive sheet. The obtained sheet has a large change in thickness under pressure, and the insulation properties may be reduced.

[0246] [Table 1]

[0247]

[0248] [Table 2]

[0249]

[0250] Since the thermally conductive mixable silicone rubber composition of the present invention is used, the thermally conductive sheets of Examples 1 to 5 have low contact thermal resistance, excellent thermal conductivity, and moderate hardness as shown in Table 1. In addition, since the thermally conductive sheet is composed of a flexible mesh reinforcement material, it also has excellent strength and less thickness change under pressure, so the insulation properties are slightly reduced (i.e., the insulation is excellent). In addition, since the thermally conductive mixable silicone rubber composition of the present invention contains an effective amount of (F) addition reaction control agent, it also has excellent long-term stability. Moreover, since the present invention is not laminated with metal films such as metal foil, there is no need to worry about increased contact thermal resistance, poor insulation, and increased manufacturing costs. In addition, by making the particle size of the thermally conductive filler (C) appropriate, continuous coating molding can be performed, and as a result, it can be manufactured in a low-cost and simple process, and the product characteristics are also stable for a long time.

[0251] Based on the above results, it can be seen that the products of the present invention have low contact thermal resistance, excellent flexibility, little reduction in insulation properties under pressure, and can be manufactured with a low cost and simple manufacturing process. However, the comparative examples that do not meet the requirements of the present invention have the following problems: large contact thermal resistance or insufficient material strength. That is, in Comparative Example 1, in which the meshes of the glass cloth were filled with the peroxide-curable composition (k) and the thermally conductive sheet was obtained by coating, the contact thermal resistance became too large. In Comparative Example 2, in which the meshes of the glass cloth were filled with the composition (l) not containing the component (A-2) and the thermally conductive sheet was obtained, the contact thermal resistance and the thickness could not be accurately measured. In Comparative Example 3, in which the meshes of the glass cloth were filled with the composition (m) containing an excessive amount of the component (C), the thermally conductive sheet was obtained, but the contact thermal resistance and the thickness could not be accurately measured. In Comparative Example 5, in which the meshes of the glass cloth were filled with the composition (o) containing a significantly excessive amount of the component (B) and the thermally conductive sheet was obtained, the component (B) that does not participate in the cross-linking reaction acts as a plasticizer, and therefore the thickness of the obtained thermally conductive sheet changes greatly under pressure, and the insulation properties may be reduced.

[0252] This specification contains the following protocols.

[0253] [1] A thermally conductive kneadable silicone rubber composition, comprising:

[0254] (A) 100 parts by mass of a linear organopolysiloxane having an alkenyl group comprising the following components (A-1) to (A-3),

[0255] (A-1) a colloidal organopolysiloxane having alkenyl groups only at both ends of the molecular chain,

[0256] (A-2) a colloidal organopolysiloxane having alkenyl groups at both ends of the molecular chain and in the side chain,

[0257] (A-3) an organopolysiloxane having two or more alkenyl groups in one molecule and being liquid at 25°C;

[0258] (B) an organohydrogenpolysiloxane comprising the following components (B-1) and (B-2): an amount such that the total amount of the hydrosilyl groups in the component (B) is 0.5 to 4.0 mol relative to 1 mol of the total amount of the alkenyl groups in the component (A)

[0259] (B-1) an organohydrogenpolysiloxane having hydrosilyl groups only in side chains of the molecular chain and having 2 to 5 hydrosilyl groups in one molecule,

[0260] (B-2) an organohydrogenpolysiloxane having two or more hydrosilyl groups in one molecule and two of these hydrosilyl groups at the ends of the molecular chain;

[0261] (C) thermally conductive filler: 150 to 2,400 parts by mass;

[0262] (E) an addition reaction catalyst: an amount of 0.01 to 1,000 ppm calculated as the atomic mass of the platinum group metal; and

[0263] (F) Addition reaction control agent: effective amount.

[0264] [2] The thermally conductive kneadable silicone rubber composition according to [1], wherein the proportion of particles having a particle size of 45 μm or more contained in the component (C) is 5% by mass or less.

[0265] [3] The thermally conductive kneadable silicone rubber composition according to [1] or [2], further comprising: 5 to 100 parts by mass of a single-terminal trialkoxysilyl-modified polysiloxane represented by the following formula (1) as (D) a wetting agent component

[0266] [Chemical formula 8]

[0267]

[0268] In formula (1), R 1 It is an alkyl group having 1 to 6 carbon atoms, and n is an integer of 5 to 100.

[0269] [4] A thermally conductive sheet comprising: a cured product of the thermally conductive kneadable silicone rubber composition according to any one of [1] to [3], and a mesh reinforcing material.

[0270] [5] The thermally conductive sheet according to [4], wherein the meshes of the mesh reinforcement material are filled.

[0271] In addition, the present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and technical solutions having substantially the same structure and producing the same technical effects as the technical concept described in the claims of the present invention are all included in the technical scope of the present invention.

Claims

1. A thermally conductive, kneadable silicone rubber composition, characterized in that: Include: (A) 100 parts by mass of a linear organopolysiloxane having an alkenyl group comprising the following components (A-1) to (A-3), (A-1) a colloidal organopolysiloxane having alkenyl groups only at both ends of the molecular chain, (A-2) a colloidal organopolysiloxane having alkenyl groups at both ends of the molecular chain and in the side chain, (A-3) an organopolysiloxane having two or more alkenyl groups in one molecule and being liquid at 25°C; (B) an organohydrogenpolysiloxane comprising the following components (B-1) and (B-2): an amount such that the total amount of the hydrosilyl groups in the component (B) is 0.5 to 4.0 mol per 1 mol of the total amount of the alkenyl groups in the component (A); (B-1) an organohydrogenpolysiloxane having hydrosilyl groups only in side chains of the molecular chain and having 2 to 5 hydrosilyl groups in one molecule, (B-2) an organohydrogenpolysiloxane having two or more hydrosilyl groups in one molecule and two of these hydrosilyl groups at the ends of the molecular chain; (C) thermally conductive filler: 150 to 2,400 parts by mass; (E) an addition reaction catalyst: an amount of 0.01 to 1,000 ppm calculated as the atomic mass of the platinum group metal; and (F) Addition reaction control agent: effective amount.

2. The thermally conductive kneadable silicone rubber composition according to claim 1, characterized in that: The proportion of particles having a particle size of 45 μm or more contained in the component (C) is 5% by mass or less.

3. The thermally conductive kneadable silicone rubber composition according to claim 1, characterized in that: The invention further comprises, as a wetting agent component (D), 5 to 100 parts by mass of a one-terminal trialkoxysilyl-modified polysiloxane represented by the following formula (1), [Chemical formula 1] In formula (1), R 1 It is an alkyl group having 1 to 6 carbon atoms, and n is an integer of 5 to 100.

4. A thermally conductive sheet, characterized in that: The invention comprises: a cured product of the heat-conductive kneadable silicone rubber composition according to claim 1, and a mesh reinforcing material.

5. The thermally conductive sheet according to claim 4, characterized in that: The meshes of the mesh reinforcement material have been filled.

Citation Information

Patent Citations

  • Heat-conductive silicone composite sheet

    JP2013095023A

  • Thermally conductive composite silicone rubber sheet

    JP2014193598A

  • Thermally conductive sheet

    JP2015233104A

  • High thermal conductivity, high insulation heat dissipation sheet

    JP2017092322A

Cited By

  • High-modulus high-elasticity heat-conducting flame-retardant silicone rubber composition and preparation method thereof

    CN121517711A